16 Variability in lumbar punctures and neuroimaging in infants less than 90 days with acute bacterial meningitis at a provincial children's hospital in Canada. (19th August 2020) - Bourne, Stephanie; Findlay, Briar; McLaughlin, Thomas; Remington, Mia
Abstract: Background: Bacterial meningitis remains a significant cause of morbidity and mortality in infants, necessitating appropriate and timely investigations and treatment. Despite this, there are no current Canadian practice guidelines outlining the recommended management of infants with bacterial meningitis beyond empiric antimicrobial choice. As bacterial meningitis remains one of the most severe infectious diseases managed by general pediatricians, it warrants an attempt at practice standardization. Objectives: The purpose of this study is to review and identify variation in the timing and frequency of lumbar punctures (LPs) and the use of neuroimaging for the management of bacterial meningitis for infants less than 90 days of age at BC Children's & Women's Hospital (BCCWH). Design/Methods: A retrospective chart review at BCCWH identified confirmed, presumed or possible bacterial meningitis in infants less than 90 days of age over a five-year period (2013-2018). Anonymized data was collected from medical charts, de-identified and stored in REDCap. Results: Eighty-one patients were included. Fifty-three percent of all patients had a delay in receiving an initial LP. The most common reasons for delays were that the patient was too unstable (42%) or that the first LP attempt was unsuccessful (26%). Forty-six percent of all patients had only one LP while 36% had at least one repeat LP. Most repeat LPs were done within 7 days of diagnosis. Twenty-nine percent of patients had an end of treatment LPs. Of all patients, 80% had neuroimaging. Head ultrasound (US) was the most commonly used imaging modality for both first image (68%) and subsequent images (64%). Seventeen percent of patients received a CT scan and 15% an MRI as their first image. In most cases, there was no clear clinical indication for imaging noted other than a diagnosis of meningitis (44%). Conclusion: This retrospective study confirms that there is variability in the management of bacterial meningitis with respect to lumbar punctures and neuroimaging in young infants. The findings demonstrate LPs are commonly delayed, and suggest a need to develop clearly defined criteria for evaluating instability before an initial LP. Furthermore, the findings raise concern regarding the common practice of ordering head ultrasound for meningitis, given lower sensitivity in detecting disease complications and therefore disputed clinical utility.